DAMPAK PENGGUNAAN TEKNOLOGI TERHADAP PERKEMBANGAN KARAKTER AFEKTIF SISWA - Hijrianti, Hijrianti; Fallah, Al-Humairah Tsaniatul; Mayora, Elsa; Priyadi , Deni; Alfarosa, Aqillah Deani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In this modern era, technological advances are very rapid among teenagers. Of course, it can also influence students' affective character. Students at SMPN 15 Mataram are no exception. The aim of this research is to determine the impact of the use of technology on the development of students' affective character. It is also possible that there will be many problems regarding pornographic videos and negative content, especially for national class 7 students. According to law number 20 of 2003 concerning the education system, the emphasis is on the importance of affective character education in the education system. The method used in this case uses a qualitative descriptive method. In this case the researcher conducted interviews, observations and documentation to obtain data. Apart from that, researchers used case study data analysis techniques. The results of the research show that the use of technology has a very big impact on developing the affective character of students at SMPN 15. However, the teachers at SMPN 15 Mataram have tried their best in this regard. Such as carry out strict supervision, namely the existence of regulations regarding the prohibition of carrying cell phones.